Struggling to belong: nativism, identities, and urban social relations in Kano and Amsterdam - Ehrhardt, D (2011)
The research problem of this thesis is to explore the effects of top-down, bureaucratic definitions of belonging and social identity on urban social relations. More specifically, the thesis analyses the ways in which the nativist categorisations of indigeneity in Kano and autochtonie in Amsterdam can help to understand the tensions between ethnic groups in these two cities. Methodologically, the study is designed as a least-similar, comparative exploration and uses mixed qualitative and quantitative methods in its case studies of Kano and Amsterdam. Theoretically, this study uses identity cleavages and identification as the mediators between policy categories and social relations. It combines social-psychological, historical, and institutional theories to link bureaucratic nativism to ethnic identities and, finally, to conflictual (or ‘destructive’) interethnic relations. The resulting theoretical argument of the thesis is that nativist policy categorisations are likely conducive to antagonism, avoidance, and conflict between groups defined as ‘natives’ and ‘settlers’. The central finding of the thesis is that both in Kano and in Amsterdam, indigeneity and autochtonie have entrenched a primordial and competitive (or ‘exclusionary’) notion of ethnic identities and have thus been conducive to interethnic antagonism, avoidance, and conflict. Introduced at a time of rapid immigration, social change, and persistent horizontal inequalities, the two top-down policy categories came to redefine urban belonging in Kano and Amsterdam. As a result, previously apolitical ethnic boundaries between ‘natives’ and ‘settlers’ became politicised, connected to exclusionary definitions of religion and class, and ranked on the basis of their claim to a primordial ‘native’ status - that is, their status as historical ‘first-comers’ in their place of residence. The categorisation and group positioning effects of nativism have, therefore, intensified the urban struggle to belong in Kano and Amsterdam. At the same time, however, the thesis underlines that ethnic conflict in Kano and Amsterdam is limited, partly because nativist forms of belonging are continuously challenged by, for example, inclusive multiculturalism in Kano and urban citizenship in Amsterdam.